Parent-infant closeness and care practices during therapeutic hypothermia in Swedish neonatal intensive care units - Bäcke, Pyrola; Axelin, Anna; Ågren, Johan; Thernström Blomqvist, Ylva (Elsevier, 2025)
Objectives
The aim of this study was to investigate care practices among Neonatal Intensive Care Units (NICU) providing Therapeutic hypothermia (TH), and more specific to investigate staff’s experiences of parental participation, presence, and possibilities of being close with their infant during TH.
Methods
A descriptive, qualitative, and quantitative study. All Swedish NICUs providing TH (n = 10) participated. Data were collected during January–April 2021 via a questionnaire followed by a semi-structured interview with the registered nurse and the neonatologist responsible for TH at each unit. Descriptive statistics were calculated, and a qualitative content analysis was performed.
Results
All NICUs allowed parents unlimited stay with their infants and were keen to support parental presence, which was a prerequisite for promoting parent-infant closeness. Standardized routines regarding the infants’ care space and course of action were described as time-efficient and staff-saving, which freed up time to focus on the families.
Conclusion
Standardized routines regarding the care space setup and the medical and caring approach, as well as the NICU environment and practices around the families, can promote or curb the possibilities of parent-infant closeness. Well-established care practices and good environmental conditions with flexibility regarding the family’s needs are therefore required.